1994
DOI: 10.1159/000168701
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hypokalemia with Antialdosterone Therapy in Gitelman’s Syndrome

Abstract: Six adult patients (4 females and 2 males, age range 26-57 years) with Gitelman’s syndrome (GS) were treated with spironolactone 200-300 mg/day (n = 5) and/or amiloride 10-30 mg/day (n = 3) for 1-18 months. The patients had hypokalemia, hyperreninemia, chloride-resistant metabolic alkalosis, renal hypomagnesemia (n = 5), and hypocalciuria (n = 5). Free water clearance studies during maximal water diuresis and furosemide administration were suggestive of a solute reabsorptive defect beyond the loop of Henle. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 16 publications
2
33
0
2
Order By: Relevance
“…Our results provided here were found in a recruitment that was regional and mainly endocrinological with phenotype and follow-up assessment. Indeed, few studies have focused on the treatment of GS (10,11), and none have been done on the clinical and biological progression of GS. Therefore, the first aim of this study was to determine the prevalence of genetically proven GS in a population of patients referred for chronic low blood potassium levels with renal potassium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provided here were found in a recruitment that was regional and mainly endocrinological with phenotype and follow-up assessment. Indeed, few studies have focused on the treatment of GS (10,11), and none have been done on the clinical and biological progression of GS. Therefore, the first aim of this study was to determine the prevalence of genetically proven GS in a population of patients referred for chronic low blood potassium levels with renal potassium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to note that aldosterone excess has been shown to be associated with renal Mg 2+ wasting, whereas hypermagnesemia may accompany aldosterone deficiency (4,41). In addition, it has been shown that the mineralocorticoid receptor antagonist spironolactone reduces urinary Mg 2+ excretion in patients with Gitelman syndrome (42,43). During thiazideinduced ECV contraction as well as in NCC -/-mice, aldosterone levels are increased (25).…”
Section: Figurementioning
confidence: 99%
“…Hypokalemia is associated with the intensity of musculoskeletal symptoms and the occurrence of more severe complications, and it has previously been shown to respond to each of three study drugs in preliminary reports. 11,15,16 Hypokalemia in patients with GS is caused by secondary consequences of the inherited inactivation of NCC in the proximal DCT, including increased sodium delivery to late DCTand cortical connecting duct and secondary renin-dependent hyperaldosteronism triggered by sodium depletion. This biologic and hormonal phenotype mimics the electrolytic consequences of chronic administration of thiazide diuretics, which specifically block NCC in the kidney.…”
Section: Discussionmentioning
confidence: 99%